Identification of stages of amelogenesis in the continuously growing mandiblular incisor of C57BL/6J male mice throughout life using molar teeth as landmarks - Bui, Ai Thu; Lukashova, Lyudmila; Verdelis, Kostas; Vasquez, Brent; Bhogadi, Lasya; Gabe, Claire M.; Margolis, Henry C.; Beniash, Elia (Frontiers in Physiology, 2023)
Continuously growing mouse incisors are widely used to study amelogenesis, since all stages of this process (i.e., secretory, transition and maturation) are present in a spatially determined sequence at any given time. To study biological changes associated with enamel formation, it is important to develop reliable methods for collecting ameloblasts, the cells that regulate enamel formation, from different stages of amelogenesis. Micro-dissection, the key method for collecting distinct ameloblast populations from mouse incisors, relies on positions of molar teeth as landmarks for identifying critical stages of amelogenesis. However, the positions of mandibular incisors and their spatial relationships with molar teeth change with age. The goal of this study was to identify with high precision these relationships throughout skeletal growth and in older, skeletally mature animals. Mandibles from 2, 4, 8, 12, 16, and 24-week-old, and 18-month-old mice, were collected and studied using micro-CT and histology to obtain incisal enamel mineralization profiles and to identify corresponding changes in ameloblast morphology during amelogenesis with respect to positions of molar teeth. As reported here, we have found that throughout active skeletal growth (weeks 2-16) the incisal apices and the onset of enamel mineralization move distally relative to molars. The position of the transition stage also moves distally. To test the accuracy of the landmarks, we micro-dissected enamel epithelium from mandibular incisors of 12-week-old animals into five segments, including (I) secretory, (II) late secretory - transition - early maturation, (III) early maturation, (IV) mid-maturation and (V) late maturation. Isolated segments were pooled and subjected to expression analyses of genes encoding key enamel matrix proteins (EMPs), Amelx, Enam and Odam, using RT-qPCR. Amelx and Enam were strongly expressed during the secretory stage (segment I), while their expression diminished during transition (segment II) and ceased in maturation (segments III, IV, V). In contrast, Odam’s expression was very low during secretion and increased dramatically throughout transition and maturation stages. These expression profiles are consistent with the consensus understanding of EMP expression. Overall, our results demonstrate the high accuracy of our landmarking method and emphasize the importance of selecting age-appropriate landmarks for studies of amelogenesis in mouse incisors.